PENGARUH KINERJA TENAGA MEDIS DAN PELAYANAN KESEHATAN TERHADAP SISTEM REPUTASI LAYANAN PUBLIK PADA PUSKESMAS METRO - Adhina Martatilova (Derivatif : Jurnal Manajemen, 2020)
This research was conducted at the Metro Health Center on November 28, 2019. This type of research uses a quantitative approach and data collection techniques using observations and questionnaires. The population in this study amounted to 90 people and analyzed using multiple linear regression with SPSS version 21. Based on the analysis it can be concluded that there is an effect of the performance of medical personnel on the public service reputation system at the Puskesmas Metro. This is because the performance of medical personnel has been good so that it can improve the public service reputation system. In addition, there is an influence of health services on the reputation system for public services in Metro Puskesmas. This is because health services have carried out well so as to improve the reputation system of public services. Then, there is an effect of the performance of medical personnel and health services simultaneously on the reputation system for public services in the Metro Puskesmas. This is because there is a maximum combination of performance of medical personnel and health services so as to be able to improve the reputation system of public services.Keywords:Medical Personnel Performance, Health Services, Public Service Reputation Systems